Recycled Wood from Organic Solid Waste: Innovation for Equitable and Sustainable Future - Nurul Mahmudah; Fabrizia Hidayatul Fadilla; Muhammad Wildan Afifi; Witdya Fatma Meilina; Desyana Olenka Margaretta (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Forests as critical ecosystems dominated by trees, face significant threats from extensive logging for infrastructure, manufacturing, and furniture industries, leading to deforestation and associated natural disasters such as floods and landslides. To address this, innovative solutions are needed to reduce reliance on forest wood. This study introduces an eco-friendly approach by developing recycled wood from organic solid waste, aligning with Sustainable Development Goals (SDGs), particularly Goal 9 (Industry, Innovation, and Infrastructure). Using an experimental method, recycled wood was produced from materials such as eggshells, sawdust, and marble waste. The process involved cleaning, drying, and pulverizing eggshells into powder, followed by oven-drying at 110°C for 45 minutes to achieve a maximum moisture content of 4%. The powder was mixed with a 60:40 polymer matrix and waste powder, with additional fillers like wood powder and marble waste, and molded into composite materials. Mechanical tests (tensile, flexural, compressive, water absorption, and density) revealed that natural fibers, such as coconut husk, enhanced mechanical strength, though water absorption remained high. The composite’s density (0.41–0.52 g/cm³) complied with SNI 03-2102-2006 standards for particleboard. This innovation not only mitigates deforestation but also fosters sustainable industry practices and economic opportunities through accessible technology, supporting equitable and sustainable development for future generations.